2020
DOI: 10.1002/cft2.20053
|View full text |Cite
|
Sign up to set email alerts
|

Crop rotation, irrigation system, and irrigation rate on cotton yield in southwestern Georgia

Abstract: Long‐term yield data would be useful for determining crop rotation, irrigation system selection, and irrigation rate for maximum production and economic sustainability. Research was conducted at the USDA–ARS National Peanut Research Laboratory's Multi‐crop Irrigation Research Farm in Shellman, GA (84°36″ W, 30°44″ N), on a Greenville fine sandy loam (a fine, kaolinitic, thermic Rhodic Kandiudult) soil with 0–2% slope. This long‐term study (2001–2013) compared three irrigation systems, three cotton (Gossypium h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In five of the seven studies, SDI had at least some benefit in cotton production, and in two studies it did not. Stated SDI benefits varied between studies but included yield increases (Sij et al, 2010;Lamm, 2016;Barnes et al, 2020;Sorensen et al, 2020), reduction in greenhouse gas (GHG) emissions (Bronson et al, 2018), and greater profitability (Sij et al, 2010). Negative responses attributed to SDI included a reduction in small rainfall event utilization (Goebel and Lascano, 2019) and a greater incidence of spider mite damage (Hollingsworth et al, 2014).…”
Section: Sdi In Comparison To Alternative Irrigation Systems For Cotton Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…In five of the seven studies, SDI had at least some benefit in cotton production, and in two studies it did not. Stated SDI benefits varied between studies but included yield increases (Sij et al, 2010;Lamm, 2016;Barnes et al, 2020;Sorensen et al, 2020), reduction in greenhouse gas (GHG) emissions (Bronson et al, 2018), and greater profitability (Sij et al, 2010). Negative responses attributed to SDI included a reduction in small rainfall event utilization (Goebel and Lascano, 2019) and a greater incidence of spider mite damage (Hollingsworth et al, 2014).…”
Section: Sdi In Comparison To Alternative Irrigation Systems For Cotton Productionmentioning
confidence: 99%
“…Other SDI cotton studies (16 when spread across multiple subcategories in table 2) focused more on evaluating a response specific for SDI or on improving SDI performance for cotton. Dripline depth, spacing, and/or orientation (Sij et al, 2010;AbdelGadir et al, 2011;Bufon et al, 2011;Sorensen et al, , 2020Bordovsky andMustian, 2012, 2020) was a topic in seven studies (table 2 spanning two Driplines [a] No. of Water…”
Section: Studies Of Sdi Responses And/or Performance Improvements For Cotton Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cotton is an extremely important strategic agricultural crop, therefore, scientific researches for studying the specific characteristics of its cultivation on irrigated lands are being executed in many countries of the world.Such studies are actively carried out in China [1][2][3], USA [4][5][6][7], Republic of Uzbekistan [8], Pakistan [9], Brazil [10], Australia [11] and India [12], where cotton is grown by sprinkling and drip irrigation in comparison with furrow irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, different irrigation systems have been developed and used for cotton production across the world with various results. In southwestern Georgia, USA, Sorensen et al [11] found sprinkler and shallow subsurface drip-irrigation methods to have a better lint yield than a subsurface drip system at full irrigation and the lint yield was the lowest in a rainfed treatment. In India, drip irrigation at the 75% level was found to have a better yield than sprinkler irrigation at full irrigation [12].…”
Section: Introductionmentioning
confidence: 99%